KNOWLEDGE LEVEL MEETING ON PREGNANT WOMEN DURING PREGNANCY NUTRITION BALANCED IN ANDRE ASTUTI BPM KARANGWUNGU KARANGDOWO KLATEN - Iin Muhayyinah; Zaenal Arifin; Arum Sekar Tanjung (STIKES DUTAGAMA KLATEN, 2014)
Background: The success of health services is determined and measured by maternal mortality and perinatal mortality Maternal nutritional status before and during pregnancy can affect fetal growth are being conceived. The occurrence of low birth weight is usually caused by premature birth or lack of supply of nutrition in the womb of time. LBW infants Klaten district in 2005 from 16 634 babies born, babies born with a low birth weight baby is no 224 (1.35%) babies born quality is highly dependent on the nutritional status of the mother before and during pregnancy. Nutritional problems often arise because of ignorance or lack of adequate information about nutrition. Objective: To determine the level of knowledge of pregnant women about balanced nutrition during pregnancy in BPM Andre Karangwungu Astuti, Karangdowo, Klaten. Research Methodology: The study is a descriptive study with cross sectional design. The research was conducted in BPM Andre Karangwungu Astuti, Karangdowo, Klaten during March s / d April 2013. The subjects in this study all pregnant women who check in BPM Andre Astuti Karangwungu. Sample using accidental sampling technique. Mengguankan data collection questionnaire enclosed. Results: The majority of respondents aged 20-30 years were 19 men (63.3%), most of the respondents have a high school education were 28 men (93.3%), most respondents work as housewives or as many as 28 people (93.3%). Respondents' knowledge about balanced nutrition during pregnancy in Independent Practice Midwife (BPM) Andre Astuti Karangwungu Karangdowo well most of the category by 29 respondents (96.7%). Conclusion: The level of knowledge of pregnant women about balanced nutrition during pregnancy in BPM Andre Karangwungu Astuti, Karangdowo, Klaten is good.